Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.18203/2320-1770.ijrcog20192434
|View full text |Cite
|
Sign up to set email alerts
|

Study of labetalol vs. methyldopa in treatment of pregnancy induced hypertension

Abstract: The major goal of antihypertensive medication in PIH is to prevent or treat severe hypertension (generally defined as blood pressure of ≥160/110mmHg) and its associated complications and to prolong pregnancy for as long as possible. 10 Methyldopa has been used for control of blood ABSTRACT Background: Hypertension is a common medical problem encountered during pregnancy and is associated with increased risk of adverse outcomes. Objective of this study was to compare efficacy and safety of Labetalol and Methyld… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Safety profile of both drugs was similar. 6 In a study comparing labetalol and methyldopa labetalol receiving women showed significant drop on mean arterial pressure and showed that labetalol is safe and efficient drug of choice while treating gestational hypertension. 7 Another study declared more hypotension observed with labetalol use irrespective of dosage and use.…”
Section: Introductionmentioning
confidence: 99%
“…Safety profile of both drugs was similar. 6 In a study comparing labetalol and methyldopa labetalol receiving women showed significant drop on mean arterial pressure and showed that labetalol is safe and efficient drug of choice while treating gestational hypertension. 7 Another study declared more hypotension observed with labetalol use irrespective of dosage and use.…”
Section: Introductionmentioning
confidence: 99%